Penerapan Aplikasi Thunkable untuk Mendukung Pembelajaran Berbasis Mobile di SMK Negeri 3 Sorong - Melda Agnes Manuhutu; Adrian Adrian; Shady Shady; Michael Michael; Oktovina Oktovina; Serli Serli (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
This service program aims to provide mentoring to students of SMK Negeri 3 Sorong through the utilization of mobile learning technology using the Thunkable application. Thunkable is a drag-and-drop-based platform that allows users to design interactive mobile applications without complex programming. The mentoring program was designed to enhance students’ digital literacy, foster creativity, and strengthen their understanding of subject materials through the development of self-made interactive media. The method employed in this activity involved a participatory approach, including workshops, technical guidance, and learning outcome evaluations. The results showed that students were able to develop simple applications tailored to their learning needs and demonstrated increased motivation and independence in the learning process. Furthermore, students gained hands-on experience in designing and implementing technology in practical contexts. This approach has proven effective in bridging the gap between the school curriculum and the technological skills required in today’s workforce. Therefore, using Thunkable as a mobile learning tool presents an innovative alternative in vocational education and training.